Sustainable project-based learning e-module: Enhancing problem-solving skills and environmental awareness - Nasrul Hakim; Dwi Kurnia Hayati; Asih Fitriana Dewi; Tika Mayang Sari; Laila Puspita (University of Muhammadiyah Malang, 2026)
Background: Education plays a crucial role in sustainable development by shaping generations who are sensitive to environmental issues and capable of addressing them. In higher education, research-based sustainable campus concepts and strategies can enhance the well-being, health, and productivity of the academic community. Objectives: This study employed a research and development design to develop a Project-Based Learning e-module integrated with Education for Sustainable Development to improve students’ problem-solving skills and environmental awareness. Methods: The e-module was developed using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Results: Validation by material experts yielded a score of 89.93, categorized as very valid, while design expert validation produced a score of 88.29, also categorized as very valid. The practicality test resulted in a score of 86%, indicating that the e-module was practical for use in learning activities. Students’ problem-solving skills achieved an N-gain score of 0.49, while environmental awareness reached 0.68, both categorized as moderate. Conclusion: These findings indicate that the developed e-module is valid, practical, and moderately effective, suggesting its potential as an innovative learning resource for promoting sustainability-oriented education in higher education contexts. It also offers a relevant instructional alternative for fostering active, contextual, and environmentally responsible learning experiences among university students effectively.